간호리더십 함양을 위한 학습성과 평가체계 연구 - 정희영(Heeyoung, Jung); 표은영(Eun Young, Pyo); 성미라(Mi Ra, Sung); 최은진(Eun-Jin, Choi); 박소영(So Young, Park) (한국간호연구학회지, 2024)
Purpose : This study aims to develop an evaluation system for assessing the learning outcomes and achievements of leadership development programs intended for personal and professional growth. Method : The research involved measuring the leadership qualities of nursing students, nursing educators, and clinical nurses through surveys, analyzing their general characteristics and nursing leadership scores. Additionally, a comparative analysis of existing leadership-related evaluation systems from 18 universities was conducted. The development of the leadership learning outcome evaluation system followed the procedures outlined in the evaluation system development. Results : The priorities of nursing leadership demands were different among nursing students, nursing educators, and clinical nurses. Nursing students identified major professional competence (4.43 points) as most crucial, while nursing educators and clinical nurses emphasized that communication skills (4.77 points, 4.82 points) were the most important. The analysis of existing leadership evaluation systems revealed a variety of components, including structure and criteria, performance standards, and achievement levels, performance levels, goal attainment, related courses and extracurricular activities, evaluation (timing, methods, tools, stakeholders, etc.), results analysis (stakeholders, disclosure status, disclosure methods, etc.), and improvements (evaluation and improvement timing). Conclusion : The program learning outcome evaluation system should undergo continuous improvement through regular analysis and feedback. This process will enhance the leadership skills of prospective nurses, enabling them to adapt to the evolving nursing and healthcare environment. KCI Citation Count: 0